John McDermott "CGIAR COVID-19 Hub work areas for coordinated responses" - McDermott, John (2021)
John McDermott POLICY SEMINAR Virtual Event - CGIAR COVID-19 Hub: Supporting National Responses to a Global Pandemic Co-Organized by IFPRI and CGIAR COVID-19 Hub